แนวทางการประเมินโครงการสร้างเสริมสุขภาพ - พุ่มสงวน, กุนนที; หงวนบุญมาก, บุญเกิด (Journal of The Royal Thai Army Nurses, 2017)
การประเมินเป็นกระบวนการรวบรวมและวิเคราะห์ข้อมูลเกี่ยวกับการดำเนินกิจกรรมและผลลัพธ์ของโครงการ เพื่อนำข้อมูลที่ได้ไปตัดสินคุณค่า ทำให้ได้สารสนเทศที่เป็นประโยชน์ต่อการปรับปรุง แก้ไข และพัฒนาโครงการให้มีประสิทธิภาพ รวมทั้งการตัดสินใจในการเลือกเกี่ยวกับการดำเนินโครงการต่อไป สำหรับการประเมินโครงการสร้างเสริมสุขภาพที่ผ่านมาพบว่า ขาดการวางแผนการประเมินอย่างเป็นระบบ ไม่มีการกำหนดขอบเขตและวัตถุประสงค์ของการประเมิน ขาดการประเมินอย่างต่อเนื่องผู้ประเมินขาดความรู้ความสามารถในการประเมิน และขาดการมีส่วนร่วมจากผู้ที่เกี่ยวข้องเข้ามามีส่วนร่วมในการประเมิน ในส่วนของเหตุผลหลักที่ต้องมีการประเมินก็เพื่อความรับผิดชอบของหน่วยงาน เพื่อการพัฒนาปรับปรุงโครงการ และเพื่อนำไปสู่การขยายผล ดังนั้นเพื่อให้ได้ข้อมูลสารสนเทศที่ถูกต้อง เชื่อถือได้ ตรงตามสภาพจริงและเป็นที่ยอมรับของผู้ที่เกี่ยวข้อง จึงต้องใช้วิธีการดำเนินงานการประเมินที่ชัดเจน และสามารถปฏิบัติได้ ซึ่งบทความนี้ได้นำเสนอแนวทางการประเมินที่เหมาะสมสำหรับนำใช้ในการประเมินโครงการสร้างเสริมสุขภาพ 3 วิธี คือ 1) การประเมินความก้าวหน้า 2) การประเมินแบบมีส่วนร่วม และ 3) การประเมินเสริมพลัง Health Promotion Program Evaluation Approach Evaluation is a process that collecting and analyzing information about a program’s activities and outcomes. Its purpose is to make value judgments about a program, to get information helping improvement its effectiveness and to inform programming decisions. For the evaluation of health promotion programs at last found lack of a systematic evaluation plan, no scope and purpose of evaluation, lack of continuous evaluation, evaluator lacked the knowledge to evaluate and lack of involvement from stakeholders involved in the evaluation. The main reasons for the evaluation are to accountability, improvement and generalization. So, to get information that is accurate, reliable and meets the actual conditions are acceptable to those involved and therefore require and approach to evaluation that clearly. This article presents three approaches for appropriate evaluating health promotion programs: 1) formative evaluation 2) participatory evaluation and 3) empowerment evaluation. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">